Assessment of food insecurity and food coping strategies among fishermen household during monsoon in Terengganu, Malaysia - Nik Nursabrina Nadia Nik Mohd Sanusi; Asma’ Ali; Khairil Shazmin Kamarudin; Hayati Mohd Yusof (Penerbit Universiti Kebangsaan Malaysia, 2018)
Most fishermen’s families have insufficient food, especially during the monsoon season. However, few studies have been done assessing their food insecurity and food coping strategies to sustain food availability. This cross-sectional study using convenience sampling was researcher administered to assess food insecurity (via Household Food Insecurity Access Scale - HFIAS) and food coping strategies (via Coping Strategies Index) among fishermen households during monsoon in Terengganu and to examine association between demographic, socioeconomic factors and household food insecurity level. This study was carried out among 80 respondents from fishermen households meeting eligible criterion and included married people aged 18-65 years old living in fisherman villages and wakaf beach areas in Kuala Nerus. The results showed that about 98.8% of the fishermen households in Terengganu were severely food insecure, and the remaining were moderately food insecure during the monsoon season. While for food coping strategies, ‘reduce amount of food cooked for meals’, ‘using less expensive food’, ‘cook whatever food is available at home’, and ‘reduce daily/monthly spending’ was the most highly adopted food coping strategies during monsoon season. There is a significant association found between household monthly income and food insecurity (χ2=2.85 p<0.05). This may indicates that household income of the fishermen do influence their food insecurity status. The most obvious finding to emerge from this study is that most of the fishermen household is experiencing food insecure during the monsoon season. Thus, more studies need to be conducted to yield further evidence in regards to household food insecurity among fishermen in other states in Malaysia especially during monsoon season.